The Role of Angkatan Bersendjata Newspaper as a Medium of Political Agitation, 1965–1967 - Muhamad Akbar Choirudin; Tubagus Umar Syarif Hadi Wibowo; Arif Permana Putra (Historia, 2027)
This study aims to examine the role of the Angkatan Bersendjata newspaper as a medium of political agitation during 1965–1967. The research employs the historical method, supported by the authoritarian press theory, political agitation, and political stability as analytical tools. The findings indicate that, following the banning of several anti-communist newspapers during the Guided Democracy period, the publication of Angkatan Bersendjata prior to the September 30th Movement of 1965 played a role in countering the propaganda agitation spread by the mass media under the control of the Indonesian Communist Party (PKI). In 1966–1967, beyond serving as a government medium during the Guided Democracy era to maintain political stability, this newspaper was also utilized to strengthen the Army’s position in controlling the government by spreading agitation aimed at preventing communist groups from regaining their place in the political arena.